2012
DOI: 10.3109/09638288.2012.720348
|View full text |Cite
|
Sign up to set email alerts
|

Reflective action assessment with a prospective clinical problem solving tool in the context of rehabilitation medicine: an illustrative case study

Abstract: Reflective action informed assessment applying ICF concepts to clinical problem solving resulted in positive gains in health-related quality of life in a stroke survivor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a case study, the reflective approach using the ICF was found to improve health-related quality of life in a patient with stroke. [ 19 ] The findings in the present study provide additional evidence that the ICF has validity as a stroke rehabilitation assessment instrument and, importantly, our study is the first to use a large sample size to assess the ICF.…”
Section: Discussionmentioning
confidence: 51%
“…In a case study, the reflective approach using the ICF was found to improve health-related quality of life in a patient with stroke. [ 19 ] The findings in the present study provide additional evidence that the ICF has validity as a stroke rehabilitation assessment instrument and, importantly, our study is the first to use a large sample size to assess the ICF.…”
Section: Discussionmentioning
confidence: 51%
“…Within the ICF model, people's functioning is explained as the result of interaction between a health condition and contextual factors (personal and environmental attributes). Some studies have applied ICF-derived tools in clinical care and the results indicate that they give an effective indication of service needs and treatment outcomes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative enquiry has the advantage to yield a first-person perspective that people bring to their lives (Wallace, 1972; Yin, 2009). Moreover, personal perspectives and narratives about their own illness impact health and functioning (Kellet, Mpofu, & Madden, 2013), perhaps more than the objective qualities of the illness (Fisher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%